The "Negro" in John Steinbeck's Of Mice and Men - Trupej, Janko (ELOPE (Ljubljana), 2015)
The present article examines the translation of racial elements in John Steinbeck's novel and play Of Mice and Men into Slovenian. Using the basic concepts of Kitty van Leuven-Zwart's comparative and descriptive models for the analysis of literary translations (1989, 1990), we examine strategies for translating terms referring to African Americans along with strategies for translating the discourse of the only African American character in Of Mice and Men. After the microstructural analysis, the effects of the shifts on the perception of this literary work are discussed, and its reception in Slovenia is examined. Although shifts are established in translations from both the socialist and the post- socialist period, in the first translation of the novel, from 1952, the macrostructure of the text was affected to a greater extent than in the modern translations of the novel and the play, both published in 2007. Because translation strategies differ substantially, possible reasons for the differences are also discussed, taking into consideration relevant historical and contemporary socio-political factors.
Keywords: premiki; prevajanje; rasizem; Steinbeck, John: Of Mice and Men; translation